The importance of the Austrian Law on Insurance Contracts in 1917 - Karel Schelle (Journal on European History of Law)
The 1917 Insurance Contract Act was an important milestone in the development of enactments in the field of liability in insurance system. However, the whole act never became effective. Above all, enactments dealing with special types of insurances have not come into force for a long time. Though, the Insurance Contract Act was indisputably important. In the period of the First Czechoslovak Republic it became the main condition of a new reform, which consisted in a new 1934 Insurance Act.